2017
DOI: 10.1093/jac/dkx267
|View full text |Cite
|
Sign up to set email alerts
|

Sustained impact of a rapid microarray-based assay with antimicrobial stewardship interventions on optimizing therapy in patients with Gram-positive bacteraemia

Abstract: A real-time AS intervention implemented alongside introduction of the Verigene BC-GP assay led to improvements in antibiotic therapy for patients with bacteraemia due to Gram-positive cocci, even after the AS intervention was discontinued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Resistance gene detection and/or rapid phenotypic testing is important for early optimization of treatment. Several studies have demonstrated that when either of these is combined with stewardship interventions, the median time to optimal therapy, especially for methicillin-susceptible S. aureus (MSSA) and Enterococcus species, can be shortened by 14 h to more than 24 h (11,13,44,45). In this study, vanA prevalence was low (n ϭ 8 vanA enterococci) among the prospective samples, and no vanB-containing enterococci were detected.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Resistance gene detection and/or rapid phenotypic testing is important for early optimization of treatment. Several studies have demonstrated that when either of these is combined with stewardship interventions, the median time to optimal therapy, especially for methicillin-susceptible S. aureus (MSSA) and Enterococcus species, can be shortened by 14 h to more than 24 h (11,13,44,45). In this study, vanA prevalence was low (n ϭ 8 vanA enterococci) among the prospective samples, and no vanB-containing enterococci were detected.…”
Section: Discussionmentioning
confidence: 67%
“…Rapid detection of the causative organism in positive blood cultures, especially when combined with antimicrobial stewardship, reduces the interval between recognition of bacteremia and appropriate therapy by 18 to 24 h or longer (11)(12)(13)(14). In a systematic review by Timbrook et al, it was determined that when the use of rapid molecular diagnostic methods in the identification of the microorganism causing bloodstream infections was combined with antimicrobial stewardship interventions, mortality risk was significantly lower than with conventional microbiology methods (15), prompting the authors to recommend their use as standard of care.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to conventional culture methods, these technological advances can optimize microbiology workflows, decrease time to result, and offer clinicians the potential to improve time to antibiotic tailoring ( 6 ). Studies of rapid PCR-based organism identification and antimicrobial resistance markers have shown improved outcomes such as shortened time to targeted therapy, reduced time to antimicrobial de-escalation, decreased costs, and reduced patient hospital length of stay (LOS) ( 7 12 ). However, these evaluations have been limited to mostly Gram-positive (GP) BSI, and two rapid blood culture diagnostic methodologies have not been compared.…”
Section: Introductionmentioning
confidence: 99%
“…However, these evaluations have been limited to mostly Gram-positive (GP) BSI, and two rapid blood culture diagnostic methodologies have not been compared. Moreover, a comparison of patient outcomes between rapid molecular ID and fast ID and phenotypic AST has yet to be published ( 7 9 , 11 ).…”
Section: Introductionmentioning
confidence: 99%